Kapitalkravet i ABL - Bör kapitalkravet avskaffas för att göra aktiebolagslagen konkurrenskraftig? - Olsson,Amanda (2021)
To form a private company in Sweden the founders are required to contribute at least SEK 25,000, according to the Swedish Companies Act. The statutory requirement for share capital has primarily been considered justified with regard to its function as creditor protection, but nowadays the Swedish legislator consider the share capital’s function as a barrier for irresponsible business owners as its primary function. These functions are, however, oppose to other socio-economic purposes, such as promoting new and small businesses. The requirement for share capital has therefor been reduced from SEK 100,000 to SEK 25,000 during the 21st century. According to the Swedish legislator, it’s important that the Swedish Companies Act appears to be competitive with other EU-countries legal systems. In order for the Swedish Companies Act to be considered competitive, it has to follow the international development in the field of company law. Since the European Court of Justice’s ruling in the Centros case, many European countries have chosen to abolish the share capital requirement. Some of these countries have chosen to maintain a creditor protection through their insolvency law, instead of within its company law. In light of the share capital’s function as creditor protection and the international development, the debate in Sweden has come to be about whether or not the Swedish legislator should abolish the requirement for share capital in the Swedish Companies Act. According to several critics, the share capital is arbitrary in the sense that it does not constitute relevant protection and that there are alternative methods for creditors to demand security for their claims today. In this essay, a discussion will be held on the reasons for abolishing as well as retaining the statutory requirement for share capital with the intention of making the Swedish Companies Act more competitive in comparison with other countries legal systems.
Keywords: Associationsrätt; Aktiebolagsrätt; Rättsekonomi